Multifunctional solid-solid phase change material based on thiolactone chemistry as well as preparation method and application of multifunctional solid-solid phase change material

Through the multifunctional solid-solid phase change material preparation method based on thiolactone chemistry, the problems of existing materials are solved, and the materials are simple to prepare, low cost and strong environmental adaptability are achieved, and excellent water, acid and alkali resistance are required, which are suitable for multifunctional fields.

CN119570043AActive Publication Date: 2025-03-07NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411851815.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing polymer solid-solid-phase change materials are difficult to prepare and have poor environmental adaptability, which cannot meet the needs of the fields of thermal energy storage and thermal management.

Method used

A multifunctional solid-solid phase change material preparation method based on thiolactone chemistry is adopted, and acrylates and fatty amines are reacted by double bond functionalized thiolactone to produce polymers containing a large number of aliphatic side groups, achieving rapid grafting reactions and preparing materials with good water, acid and alkali resistance.

Benefits of technology

It realizes the preparation of materials with simple cost, low cost, strong environmental adaptability, and excellent water, acid and alkali resistance. The phase change enthalpy and temperature can be controlled and adjusted. It is suitable for multifunctional fields such as energy storage, infrared stealth, and shape memory.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570043A_ABST
    Figure CN119570043A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional solid-solid phase change material based on thiolactone chemistry and a preparation method and application thereof, and relates to the technical field of high polymer materials. The method comprises the following steps: dissolving double-bond functionalized thiolactone and acrylate in an organic solvent A, adding a free radical initiator, and reacting to obtain a polymer PTA; dissolving PTA in an organic solvent B, adding aliphatic amine, aliphatic acrylate and a cross-linking agent, and uniformly mixing to obtain a mixed solution; and heating the mixed solution to 60-80 DEG C, and reacting for 1-2 hours to obtain the solid-solid phase change material. The solid-solid phase change material prepared by the invention shows multiple functions of infrared stealth, reversible anti-counterfeiting, shape memory and the like. The integration of the characteristics provides a wide prospect for developing a next-generation high-performance intelligent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a multifunctional solid-solid phase change material based on thiolactone chemistry, and a preparation method and application thereof. Background Art

[0002] Phase change materials have attracted widespread attention due to their potential applications in thermal management, energy storage, and smart surfaces. Traditional solid-liquid phase change materials cannot be used directly due to their easy leakage at high temperatures and the need for additional high-cost material packaging. Solid-solid phase change materials store thermal energy through a direct reversible phase change between a crystal (solid) or semi-crystalline phase and another amorphous (solid), semi-crystalline or crystalline phase. It has the advantages of maintaining solid-state properties during the phase change process, no liquid leakage, small volume change, no phase separation, and low supercooling. It is a type of phase change material with development potential.

[0003] The solid-solid phase change materials currently under research mainly include small molecule polyols, inorganic salts and polymers. Small molecule polyols have large phase change enthalpy and moderate phase change temperature, but their cyclic stability and mechanical properties are poor. The most prominent advantages of inorganic salt solid-solid phase change materials are high phase change enthalpy and flame retardant properties, but they are expensive and the preparation process is environmentally polluting. The essence of polymer solid-solid phase change materials is to incorporate the components of solid-liquid phase change into the macromolecular skeleton through grafting, crosslinking, copolymerization and other methods. When the phase change component is melted, the macromolecular skeleton restricts the molecular movement of the phase change component, so that the entire material remains in a solid state. Polymer solid-solid phase change materials have adjustable phase change enthalpy, suitable phase change temperature and certain mechanical strength, and are truly usable solid-solid phase change materials.

[0004] The phase change elements of mainstream polymer solid-solid phase change materials are polyethylene glycol and fatty acids. Among them, polyethylene glycol solid-solid phase change materials are prepared into polyurethane by using polyethylene glycol as the molecular soft segment and isocyanate as the molecular chain extender. Fatty acid solid-solid phase change materials are prepared into block copolymers by copolymerizing fatty acids with other monomers. This type of material takes a long time to prepare, the process is complicated, and the raw materials are highly toxic. Moreover, due to the characteristics of the molecular structure, the carbamate bond and carboxyl group are very easy to absorb water, which limits their application in humid environments.

[0005] Therefore, developing and designing a solid-solid phase change material that is simple to prepare, low-cost, environmentally adaptable and widely used is of great significance for the future fields of thermal energy storage and thermal management. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problem that the existing polymer-based solid-solid phase change materials are difficult to prepare and have poor environmental adaptability. The present invention provides a multifunctional solid-solid phase change material based on thiolactone chemistry and its preparation method and application. The polymer PTA prepared by the method contains a large number of thiolactone groups. Thiolactone can react with fatty amines to quickly open the ring, and the thiol group released in situ can react with double bonds to click. Therefore, the polymer PTA can quickly react with fatty amines and aliphatic acrylates to generate a solid-solid phase change material with a large number of aliphatic side groups. The presence of aliphatic side groups ensures its phase change ability while being hydrophobic, preventing water molecules from destroying the polymer network, so the material has good water and acid and alkali resistance.

[0007] The first object of the present invention is to provide a method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry, comprising the following steps: The double-bond functionalized thiolactone and acrylate are dissolved in an organic solvent A, and a free radical initiator is added to obtain a polymer PTA through reaction; Dissolve PTA in organic solvent B, add aliphatic amine, aliphatic acrylate and a crosslinking agent, mix well, and obtain a mixed solution; The mixed solution is heated to 60-80°C and reacted for 1-2 h to obtain a solid-solid phase change material.

[0008] Preferably, the double bond functionalized thiolactone has the following structural formula:

[0009] In the formula, X is an alkyl group or a heteroalkyl group.

[0010] Preferably, the double-bond functionalized thiolactone is prepared by reacting thiolactone hydrochloride with a double-bond acyl halide, and the synthesis route is as follows:

[0011] Wherein, Z is a halogen element; X is an alkyl group or a heteroalkyl group.

[0012] Preferably, the molar ratio of the double-bond functionalized thiolactone to the acrylate is 1:0-0.3.

[0013] Preferably, the acrylate is ethyl acrylate, hydroxyethyl acrylate, n-butyl acrylate or hexyl acrylate; the free radical initiator is azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate or di-tert-butyl peroxide.

[0014] Preferably, the amount of the fatty amine added is 0.8-1.6 times that of PTA, the amount of the aliphatic acrylate added is 1.1-1.8 times that of PTA, and the amount of the crosslinking agent added is 0.1-0.6 times that of PTA; Wherein, the fatty amine is one or more of dodecylamine, tetradecylamine, hexadecylamine and octadecylamine; The aliphatic acrylate is one or more of tetradecyl acrylate, hexadecyl acrylate, and octadecyl acrylate; The crosslinking agent is a diamine compound or a diamine polymer.

[0015] Preferably, the diamine compound is hexamethylenediamine or isophoronediamine; and the diamine polymer is polyetheramine 400, polyetheramine 800 or polyetheramine 2000.

[0016] Preferably, the organic solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, dichloromethane, and 1,4-dioxane; The organic solvent B is N,N-dimethylformamide and / or N,N-dimethylacetamide.

[0017] A second object of the present invention is to provide a multifunctional solid-solid phase change material based on thiolactone chemistry.

[0018] The third object of the present invention is to provide a multifunctional solid-solid phase change material based on thiolactone chemistry for use in the fields of energy storage, infrared stealth, shape memory or intelligent anti-counterfeiting.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a multifunctional solid-solid phase change material based on thiolactone chemistry, and a preparation method and application thereof. The present invention utilizes the easy ring opening property of thiolactone to react thiolactone copolymer with aliphatic amine and aliphatic acrylate. It is possible to achieve two-component grafting at the same site, and finally prepare a polymer containing a large number of aliphatic side groups. The aliphatic side groups crystallize in a solid state at room temperature and melt when heated, but the polymer network will limit the free movement of the aliphatic side groups, so that the material after phase change still maintains shape stability. At the same time, a large number of aliphatic side groups make the material have a certain hydrophobicity, preventing water molecules from destroying the polymer network, so the material has a certain water and acid and alkali resistance.

[0020] The present invention can realize controllable adjustment of the phase change enthalpy of the material at 20-100 J / g, the phase change temperature at 30-70°C, the modulus at 0.24-130 MPa, and the strength at 0.3-2.7 MPa by selecting the aliphatic amine and the aliphatic acrylate.

[0021] The solid-solid phase change material prepared by the present invention exhibits excellent water resistance, acid resistance and alkali resistance. The material can still maintain more than 95% of the mechanical properties and phase change enthalpy after being immersed in 0.01 mol / L HCl, H2O and 0.001 mol / L KOH for 12 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the phase change enthalpy of the solid-solid phase change material provided in Examples 1 to 4.

[0023] Figure 2 It is a physical diagram of the phase transition process of the solid-solid phase change material provided in Examples 1 to 4.

[0024] Figure 3 This is a mechanical property test of the solid-solid phase change material provided by Examples 1 to 4 under 20°C conditions.

[0025] Figure 4 The solid-solid phase change material provided in Example 2 has water resistance and acid and alkali resistance.

[0026] Figure 5 This is the shape memory ability of the solid-solid phase change material provided in Example 4.

[0027] Figure 6 The solid-solid phase change material provided in Examples 2 to 4 has infrared stealth performance under sunlight.

[0028] Figure 7 This is the human body infrared stealth performance of the solid-solid phase change material provided in Example 4.

[0029] Figure 8 It is the synergistic reversible imaging capability of the solid-solid phase change materials provided in Example 2 and Example 4.

[0030] Fig. 9 This is the phase change object of Comparative Example 1. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0032] The purpose of the present invention is to provide a multifunctional solid-solid phase change material based on thiolactone chemistry, a preparation method and application thereof, and a thiolactone copolymer is synthesized based on a biomass thiolactone. The copolymer can be in situ grafted with aliphatic amines and aliphatic acrylates through thiolactone ring opening. Due to the presence of the macromolecular skeleton, the molecular motion of aliphatic amines and aliphatic acrylates is restricted after the phase change, so the entire material remains in a solid state. By selecting different aliphatic amines and aliphatic acrylates, controllable adjustment of the phase change temperature and phase change enthalpy can be achieved in a wide range. Its phase change temperature is 30~70℃, and the phase change enthalpy is 20~100 J / g. In addition, this solid-solid phase change material also exhibits multifunctional properties such as infrared stealth, reversible anti-counterfeiting and shape memory. The integration of these characteristics provides broad prospects for the development of the next generation of high-performance smart materials.

[0033] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry, comprising the following steps: The double-bond functionalized thiolactone and acrylate are dissolved in an organic solvent A, and a free radical initiator is added to obtain a polymer PTA through reaction; Dissolve PTA in organic solvent B, add aliphatic amine, aliphatic acrylate and a crosslinking agent, mix well, and obtain a mixed solution; The mixed solution is heated to 60-80°C and reacted for 1-2 h to obtain a solid-solid phase change material.

[0034] In an embodiment, double-bond functionalized thiolactone and acrylate are dissolved in organic solvent A and reacted for 4 h. The obtained product is purified and then dissolved in organic solvent B, and then mixed with aliphatic amine and aliphatic acrylate and reacted at elevated temperature to obtain a solid-solid phase change material.

[0035] The present invention utilizes the property of easy ring opening of thiolactone to react thiolactone copolymer with aliphatic amine and aliphatic acrylate to realize double-component grafting at the same site, and finally prepares a polymer containing a large number of aliphatic side groups.

[0036] Wherein, the structural formula of the double bond functionalized thiolactone is as follows:

[0037] In the formula, X is an alkyl group or a heteroalkyl group.

[0038] The double-bond functionalized thiolactone is prepared by reacting thiolactone hydrochloride with a double-bond acyl halide, and the synthesis route is as follows:

[0039] Wherein, Z is a halogen element; X is an alkyl group or a heteroalkyl group.

[0040] The molar ratio of the double-bond functionalized thiolactone to the acrylate is 1:0.01-0.3.

[0041] The acrylic acid ester is ethyl acrylate, hydroxyethyl acrylate, n-butyl acrylate or hexyl acrylate; the free radical initiator is azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate or di-tert-butyl peroxide.

[0042] The amount of the fatty amine added is 0.8-1.6 times that of PTA, the amount of the aliphatic acrylate added is 1.1-1.8 times that of PTA, and the amount of the crosslinking agent added is 0.1-0.6 times that of PTA.

[0043] Wherein, the fatty amine is one or more of dodecylamine, tetradecylamine, hexadecylamine and octadecylamine; The aliphatic acrylate is one or more of tetradecyl acrylate, hexadecyl acrylate, and octadecyl acrylate; The crosslinking agent is a diamine compound or a diamine polymer.

[0044] The diamine compound is hexamethylenediamine or isophoronediamine; the diamine polymer is polyetheramine 400, polyetheramine 800 or polyetheramine 2000.

[0045] The organic solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, dichloromethane, and 1,4-dioxane; The organic solvent B is N,N-dimethylformamide and / or N,N-dimethylacetamide.

[0046] A second aspect of the present invention provides a multifunctional solid-solid phase change material based on thiolactone chemistry.

[0047] The third aspect of the present invention provides a multifunctional solid-solid phase change material based on thiolactone chemistry for use in the fields of energy storage, infrared stealth, shape memory or intelligent anti-counterfeiting.

[0048] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0049] Example 1 (1) Dissolve 4.1000 g of acrylamide thiolactone and 0.768 g of butyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0082 g of azobisisobutyronitrile, bubble N2 for 30 min, raise the temperature to 70°C and react for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0050] (2) Dissolve 0.5 g of the above polymer in 1 g of N,N-dimethylformamide, add 0.445 g of tetradecylamine and 0.5478 g of tetradecyl acrylate. Pour the mixed solution into a polytetrafluoroethylene mold and heat to 80°C for 5 min.

[0051] (3) Add 0.3 g of polyetheramine 2000 to the above mixed solution and continue the reaction at 80 °C for 2 h to obtain the solid-solid phase change film PTA-C 14 -C 14 .

[0052] Example 2 (1) Dissolve 4.1000 g of acrylamide thiolactone and 0.768 g of butyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0082 g of azobisisobutyronitrile, bubble N2 for 30 min, raise the temperature to 70°C and react for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0053] (2) Dissolve 0.5 g of the above polymer in 1 g of N,N-dimethylformamide, add 0.445 g of tetradecylamine and 0.6113 g of hexadecyl acrylate. Pour the mixed solution into a polytetrafluoroethylene mold and heat to 60°C for 5 min.

[0054] (3) Add 0.3 g of polyetheramine 2000 to the above mixed solution and continue the reaction at 60 °C for 2 h to obtain the solid-solid phase change film PTA-C 14 -C 16 .

[0055] Example 3 (1) Dissolve 4.1000 g of acrylamide thiolactone and 0.768 g of butyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0082 g of azobisisobutyronitrile, bubble N2 for 30 min, raise the temperature to 70°C and react for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0056] (2) Dissolve 0.5 g of the above polymer in 1 g of N,N-dimethylformamide, add 0.5366 g of hexadecylamine and 0.6113 g of hexadecyl acrylate, pour the mixed solution into a polytetrafluoroethylene mold and heat to 70°C for 5 min.

[0057] (3) Add 0.3 g of polyetheramine 2000 to the above mixed solution and continue the reaction at 70 °C for 2 h to obtain a solid-solid phase change film PTA-C 16 -C 16 .

[0058] Example 4 (1) Dissolve 4.1000 g of acrylamide thiolactone and 0.768 g of butyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0082 g of azobisisobutyronitrile, bubble N2 for 30 min, raise the temperature to 70°C and react for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0059] (2) Dissolve 0.5 g of the above polymer in 1 g of N,N-dimethylformamide, add 0.5989 g of octadecylamine and 0.6623 g of octadecyl acrylate, pour the mixed solution into a polytetrafluoroethylene mold and heat to 60°C for 5 min.

[0060] (3) Add 0.3 g of polyetheramine 2000 to the above mixed solution and continue the reaction at 60 °C for 2 h to obtain the solid-solid phase change film PTA-C 18 -C 18 .

[0061] Example 5 (1) Dissolve 10.2670 g of acrylamide thiolactone and 1.7418 g of hydroxyethyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0205 g of azobisisobutyronitrile, bubble N2 for 30 min, and heat to 70 °C for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0062] (2) Dissolve 0.5 g of the above polymer in 1 g of N,N-dimethylformamide, add 0.5989 g of octadecylamine and 0.6623 g of octadecyl acrylate, pour the mixed solution into a polytetrafluoroethylene mold and heat to 65°C for 5 min.

[0063] (3) Add 0.12 g of polyetheramine 800 to the above mixed solution and continue the reaction at 65 °C for 2 h to obtain the solid-solid phase change film PTA-C 18 -C 18 .

[0064] Example 6 (1) Dissolve 10.2670 g of acrylamide thiolactone and 1.7418 g of hydroxyethyl acrylate in 50 mL of N,N-dimethylformamide, add 0.0205 g of azobisisobutyronitrile, bubble N2 for 30 min, and heat to 70 °C for 5 h. After the solution is evaporated to remove the solvent, the obtained product is precipitated in methanol, and the precipitate is collected and dried.

[0065] (2) Dissolve 0.5 g of the above polymer in 1 g of N, N-dimethylformamide, add 0.4445 g of tetradecylamine and 0.6051 g of hexadecyl acrylate. Pour the mixed solution into a polytetrafluoroethylene mold and heat to 60°C for 5 min.

[0066] (3) Add 0.06 g of polyetheramine 400 to the above mixed solution and continue the reaction at 60 °C for 2 h to obtain a solid-solid phase change film PTA-C 14 -C 16 .

[0067] Comparative Example 1 (1) Dissolve 1 g of octadecylamine, 1 g of octadecyl acrylate and 0.5 g of polyetheramine 400 in 5 mL of N, N-dimethylformamide and heat the mixture to 80 °C.

[0068] (2) After the above substances are completely dissolved without phase separation, the solvent is evaporated at 80°C to obtain a eutectic phase change material.

[0069] In order to illustrate the relevant properties of the solid-solid phase change material provided by the present invention, it is described in conjunction with the accompanying drawings.

[0070] Figure 1 It is the DSC curve of the solid-solid phase change material provided in Examples 1 to 4. It can be seen from the figure that all materials absorb heat when the temperature rises and release heat when the temperature drops. And by adjusting the polymer side chain structure, a phase change material with a phase change temperature of 30 to 70°C and a phase change enthalpy of 20 to 100 J / g can be obtained.

[0071] Figure 2 This is a physical diagram of the phase change process of the solid-solid phase change material provided in Examples 1 to 4. The material gradually changes from an opaque film to a transparent film during the heating process, and there is no liquid leakage during the phase change process.

[0072] Figure 3 This is a mechanical property test of the solid-solid phase change material provided by Examples 1 to 4 at 20° C. As can be seen from the figure, by adjusting the side chain of the polymer, the material can be transformed from hard to soft.

[0073] Figure 4 This is a mechanical property test of the solid-solid phase change material provided in Example 2 after being immersed in a pH=3 HCl solution, a pH=10 NaOH solution and water for 2 hours. Due to the large amount of hydrophobic alkyl side chains in the polymer, the material exhibits excellent water resistance, acid resistance and alkali resistance.

[0074] Figure 5 It is the shape memory ability of the solid-solid phase change material provided in Example 4. When the material is heated, a phase transition occurs, and the polymer chain segments have a certain free movement ability. In this state, a new shape is given to the material and it is quickly cooled, and the original network chain structure does not change. At this time, the polymer is in a restricted crystallization state. When the temperature is raised again, the polymer chain segments regain their ability to move, and the material returns to its original shape.

[0075] Figure 6It is the infrared stealth capability of the solid-solid phase change material under sunlight provided in Examples 2 to 4. When the target object and the phase change material are in the shadow, the material temperature is close to the ambient background temperature, and there is almost no image under the infrared camera. When the target object and the phase change material are in sunlight at the same time, the target object absorbs the heat of the sunlight and heats up rapidly, while the phase change material has a phase change temperature that is equivalent to the ambient background temperature, so the temperature of the heat absorption process remains unchanged, and the phase change material has no image under the infrared camera. In this state, the phase change material is placed above the target object, and the infrared radiation of the target object is absorbed by the phase change material, thereby achieving infrared stealth of the target object under sunlight.

[0076] Figure 7 This is the infrared stealth capability of the phase change material provided in Example 4. Different from the sunlight stealth of the target object, the human body as a heat source always has a temperature difference with the natural environment, so a very clear image of the human body can be seen under an infrared camera. When the phase change material is placed on the palm of the hand, the phase change material absorbs the infrared heat radiation of the human body, so that the covered part is the same color as the background under the infrared camera, thereby achieving infrared stealth of the human body.

[0077] Figure 8 It is the synergistic reversible imaging ability of the solid-solid phase change materials provided in Example 2 and Example 4. Solid-solid phase change materials with different phase change temperatures are prepared by adjusting the side chain structure. The two materials are placed in a certain pattern. When the temperature is raised, the material with a lower phase change temperature undergoes a phase change first and becomes transparent, leaving a "1803" pattern on the glass plate. After the temperature continues to rise, all materials undergo a phase change and become transparent, and the pattern disappears. When the temperature is lowered, the "1803" pattern is displayed again due to the difference in crystallization temperature.

[0078] Fig. 9 This is the phase change object of comparative example 1. The material is a white solid at room temperature, and the material undergoes a phase change after being heated to 60°C. Due to the lack of additional packaging, the solid-liquid phase change of the material will cause the liquid to flow over a large area and lose its shape stability.

[0079] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry, characterized in that: The following steps are involved: The double-bond functionalized thiolactone and acrylate are dissolved in an organic solvent A, and a free radical initiator is added to obtain a polymer PTA through reaction; Dissolve PTA in organic solvent B, add aliphatic amine, aliphatic acrylate and a crosslinking agent, mix well, and obtain a mixed solution; The mixed solution is heated to 60-80°C and reacted for 1-2 h to obtain a solid-solid phase change material.

2. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 1, characterized in that: The structural formula of the double bond functionalized thiolactone is as follows: In the formula, X is an alkyl group or a heteroalkyl group.

3. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 2, characterized in that: The double-bond functionalized thiolactone is prepared by reacting thiolactone hydrochloride with a double-bond acyl halide, and the synthesis route is as follows: Wherein, Z is a halogen element; X is an alkyl group or a heteroalkyl group.

4. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 1, characterized in that: The molar ratio of the double-bond functionalized thiolactone to the acrylate is 1:0-0.

3.

5. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 1, characterized in that: The acrylic acid ester is ethyl acrylate, hydroxyethyl acrylate, n-butyl acrylate or hexyl acrylate; the free radical initiator is azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate or di-tert-butyl peroxide.

6. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 1, characterized in that: The amount of the fatty amine added is 0.8-1.6 times that of PTA, the amount of the aliphatic acrylate added is 1.1-1.8 times that of PTA, and the amount of the crosslinking agent added is 0.1-0.6 times that of PTA; Wherein, the fatty amine is one or more of dodecylamine, tetradecylamine, hexadecylamine and octadecylamine; The aliphatic acrylate is one or more of tetradecyl acrylate, hexadecyl acrylate, and octadecyl acrylate; The crosslinking agent is a diamine compound or a diamine polymer.

7. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 6, characterized in that: The diamine compound is hexamethylenediamine or isophoronediamine; the diamine polymer is polyetheramine 400, polyetheramine 800 or polyetheramine 2000.

8. The method for preparing a multifunctional solid-solid phase change material based on thiolactone chemistry according to claim 1, characterized in that: The organic solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, dichloromethane, and 1,4-dioxane; The organic solvent B is N,N-dimethylformamide and / or N,N-dimethylacetamide.

9. A multifunctional solid-solid phase change material based on thiolactone chemistry prepared by the method according to any one of claims 1 to 8.

10. An application of the multifunctional solid-solid phase change material based on thiolactone chemistry as claimed in claim 9 in the fields of energy storage, infrared stealth, shape memory or intelligent anti-counterfeiting.

Citation Information

Patent Citations

  • Photopolymerization solid-solid energy storage phase-change material and preparation method thereof

    CN102516951A

  • Fast and efficient programming shape memory material and preparation method thereof

    CN116143969A

  • High-toughness self-repairing supramolecular polyurethane elastomer based on thiolactone chemistry and preparation method of high-toughness self-repairing supramolecular polyurethane elastomer

    CN116217889A